PELAKSANAAN PENGAWASAN DI TAMAN BUNGA IMPIAN OKURA KOTA PEKANBARU - Dhinda Indri Rahmadani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Pekanbaru has the opportunity to become a leading destination that can be further developed, because there are also many tourist attractions in Pekanbaru City. One of which is in the Rumbai subdistrict, East Rumbai to be precise, such as : the okura dream flower garden, horse riding rides, mangrove forest, and fishing parks. This study aims to determine the implementation of supervision in the okura dream flower garden Pekanbaru City. Based on the research that has been done, this research uses qualitative descriptive approach. The subject of this research were the Pekanbaru City Tourism Office and Pokdarwis at the okura dream flower garden Pekanbaru City. Data collection is done by studying documentation, observation, interview and documents. The result of the study show that there are 3 supervisio at the okura dream flower garden, namely : security supervision, supervision of all flowers, supervision of facilities, carried out independently and have constraints on the lack of unds they have and the lack of number of workers. Keyword : Flower Garden, Supervision, Okura High Cliff Village.